2014
DOI: 10.1021/pr5005136
|View full text |Cite
|
Sign up to set email alerts
|

Functional Mapping of the Zebrafish Early Embryo Proteome and Transcriptome

Abstract: Zebrafish is a popular system for studying vertebrate development and disease that shows high genetic conservation with humans. Molecular level studies at different stages of development are essential for understanding the processes deployed during ontogeny. Here, we performed comparative analysis of the whole proteome and transcriptome of the early stage (24 h post-fertilization) zebrafish embryo. We identified 8363 proteins with their approximate cellular abundances (the largest number of zebrafish embryo pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 87 publications
0
25
0
Order By: Relevance
“…Although the dechorionation/deyolking procedure generally resulted in a substantial increase in the number of identified proteins, it also resulted in a loss of certain proteins as compared to the non-deyolked counterparts ( Figure 3A), similarly to a study on 5 dpf zebrafish larvae [21]. Most of the previous proteomic studies did not address the problem of protein depletion due to the deyolking process, and they only used deyolked embryos for the analyses [16,21,22]. In the present study, approximately 30% of the proteins at cleavage stages and 12% at oblong and bud stages were not identified after the deyolking (Figure 3, Supplementary File 1).…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Although the dechorionation/deyolking procedure generally resulted in a substantial increase in the number of identified proteins, it also resulted in a loss of certain proteins as compared to the non-deyolked counterparts ( Figure 3A), similarly to a study on 5 dpf zebrafish larvae [21]. Most of the previous proteomic studies did not address the problem of protein depletion due to the deyolking process, and they only used deyolked embryos for the analyses [16,21,22]. In the present study, approximately 30% of the proteins at cleavage stages and 12% at oblong and bud stages were not identified after the deyolking (Figure 3, Supplementary File 1).…”
Section: Discussionmentioning
confidence: 85%
“…To reduce the abundance of yolk proteins, deyolking protocols are employed; they have been used in a number of studies on zebrafish embryos and larvae from 3.3 h post-fertilization (hpf) to from 3.3 h post-fertilization (hpf) to 7 days post-fertilization (dpf) [16,[19][20][21]. In most extensive studies to date, 5267 and 8363 proteins were identified in zebrafish deyolked embryos at 24 hpf [22,23].…”
Section: Introductionmentioning
confidence: 99%
“…It should be noted that understanding correlations, or lack thereof, between levels of transcripts and their corresponding proteins is fundamentally important for any systematic interpretation of complex molecular networks 64 . The high spatial resolution gene expression data set may enable more precise prediction of quantitative transcript-protein associations, although correlations can vary depending on the protein function, developmental stage, and cell/tissue type, as shown in metazoans 65 , 66 and plants 67 , 68 .…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, it was recently shown that dormant stem cell populations have low metabolic activity, and this is required to maintain the hematopoietic system during aging and periods of intense stress ( Cabezas-Wallscheid et al, 2017 ). Although proteomics and metabolomics methods have not yet been extensively explored in zebrafish, particularly in the hematopoietic system, some studies have reported differences between transcript and protein levels in multiple genes by using proteomic analyses either in whole zebrafish embryos or in specific cell populations during regeneration ( Alli Shaik et al, 2014 ; Baral et al, 2014 ; Rabinowitz et al, 2017 ). Metabolomics has proven useful to understand the neurological damage resulting from chemical perturbations in zebrafish embryos ( Ong et al, 2009 ; Rabinowitz et al, 2017 ; Roy et al, 2017 ).…”
Section: Identification Of Novel Regulatory Mechanisms Of Normal and mentioning
confidence: 99%